Effectiveness of Holland's RIASEC-Based Career Counseling in Reducing Decision-Making Difficulties among Vocational Students in Bali - Gede Danu Setiawan (Universitas PGRI Yogyakarta, 2026)
The prevalence of Career Decision-Making Difficulties (CDM) among vocational high school students remains a significant concern, particularly in developing regions where access to structured career guidance is limited. This study examines the effectiveness of John L. Holland's RIASEC-based career counseling in reducing CDM among vocational students in Bali Province, Indonesia. A quantitative pre-experimental design with a one-group pretest-posttest approach was employed. The sample comprised 273 eleventh-grade students selected from 26 schools across Bali using purposive random sampling. Data were collected using a validated Career Decision-Making Difficulties Questionnaire and analyzed using a paired-sample t-test. The intervention consisted of at least three structured RIASEC counseling sessions delivered individually or in groups. Results demonstrated a substantial and statistically significant increase in career decision-making scores from pretest (M = 28.47) to posttest (M = 77.80), with t_calculated (4.76) exceeding t_table (1.65), thereby rejecting the null hypothesis. These findings establish that Holland's RIASEC model, operationalized through a systematic three-stage syntax, effectively reduces CDM by enhancing students' self-understanding and aligning their interests with suitable career pathways. This study contributes original evidence from a collectivist cultural context, addressing a critical gap in the literature. The findings offer practical implications for guidance and counseling teachers, school policy development, and counselor education programs, while underscoring the need for longitudinal research to assess sustained career outcomes. Keywords: career counseling, career decision-making difficulties, Holland's theory, RIASEC model, vocational high school students